Synergistic Stability and Bioavailability of Anthocyanin Complexes in Hibiscus Fortified Orange Ready to Serve Beverages - Sachi Pal; Vaibhav Patil; Srushti Phule; Revati Deshmukh; Nauman Belim; Aditi Masurkar (Archives of Current Research International, 2025)
RTS beverage is a ready-to-serve beverage prepared to increase fruit juice’s shelf life. RTS beverage is prepared by selecting fresh ripe fruits to extract the juice and adding ingredients like preservatives, water, and citric acid according to FSSAI regulations. A study was performed to increase the nutritional value of the orange RTS by fortification with Hibiscus flower extract.2%, 4%, and 6% extract were added to each of the three RTS respectively. Hibiscus flower extract was prepared by collecting Hibiscus flowers and drying the flower’s petals at 60°C for 1.5 hours further crushing it manually and preparing the extract by boiling it in hot water. Anthocyanin being water soluble was leached into the water. Hibiscus flower extract is rich in polyphenols and antioxidant properties. Polyphenols in Hibiscus extract have many health benefits such as fighting cancer-causing cells and promoting heart health. Antioxidants like anthocyanins, beta-carotene, and vitamin C help fight free radicals. Further tests were conducted to evaluate the polyphenol value, antioxidant content, acidity, and TSS of the orange fruit RTS. The polyphenol content was increased according to the test of the fortified sample also enhancing its Nutritional value.